Reflections on Puerto Rican History: Aspira in the Sixties and the Coming of Age of the Stateside Puerto Rican Community - Louis Nuñez (Centro Journal, 2009)
This paper focuses on the development of Aspira from a small organization to the first national educational and leadership development institution in the Puerto Rican community in the United States. Written from the perspective of an early staff member who became the executive director and later the first national executive director of Aspira, the paper assesses the impact that Aspira had in the emergence of a new leadership among the youth of the rapidly growing stateside Puerto Rican community.